Studying relative sea level change and correlative adaptation of coastal structures on submerged Roman time ruins nearby Naples (southern Italy). (20th January 2019) - Aucelli, Pietro; Cinque, Aldo; Mattei, Gaia; Pappone, Gerardo; Rizzo, Angela
Abstract: The southwestern periphery of Naples is dominated by the Posillipo promontory, an elongated tuffaceous ridge belonging to Campi Flegrei active volcanic complex (CF). The central caldera of CF is well-known for offering a rich geoarchaeological record of the vertical ground movements occurred since Roman times, as the case of the Portus Julius ruins (37 BC) presently found between 10 and 5 m bsl and the Middle Ages Lithophaga perforations at about 7 m asl on the marble columns of the mecellum previously interpreted as Serapaeum (Morhange et al., 2006). In the last one hundred years, several unrest episodes have been precisely reconstructed in the same area (Del Gaudio et al., 2010; De Martino et al., 2014), but never before, vertical ground movements have been presumed along the Posillipo hill, positioned over the caldera rim. This paper deals with a research aimed to evaluate the vertical movements at Posillipo area during the last two millennia, by means of geomorphological and geophysical surveys in three submerged archaeological sites: Nisida Roman port, Marechiaro Roman port and ruins offshore Villa Rosebery. By precisely measuring the present submersion of all remains found in those sites, two relative paleo-sea levels have been detected: one for the 1st century BC at −4.4/-5 ±0.5 m and another for the 1st century AD at −3 ±0.5 m. Only seventeen centimetres of the difference between the two paleo-sea levels is attributable to eustasy (Lambeck et al., 2011), while the rest (2 ± 0.5 m) has to be ascribed to a phase of accelerated subsidence which has still to be precisely dated and whose duration could have been as short as few years or decades. The additional subsidence suffered by the area after the 1st century AD was calculated to be 2.0 ± 0.5 m. Even though the ground deformations reconstructed in the Posillipo area appear less strong than those recognized inside the CF caldera, they prove that vertical movements of volcanic origin were not always confined inside the caldera rim. In terms of human adaptation, the observed archaeological evidence narrates that Palazzo degli Spiriti was restored closing the rooms submerged by sea, the breakwater of Marechiaro and the villa foundations at Rosebery were probably raised, in response to the relative sea level rise.